2006
DOI: 10.1593/neo.06445
|View full text |Cite
|
Sign up to set email alerts
|

Role of Desumoylation in the Development of Prostate Cancer

Abstract: SUMO is a novel ubiquitin-like protein that can covalently modify a large number of nuclear proteins. SUMO modification has emerged as an important regulatory mechanism for protein function and localization. Sumoylation is a dynamic process that is mediated by activating (E1), conjugating (E2), and ligating (E3) enzymes and is readily reversed by a family of SUMO-specific proteases (SENPs). Since SUMO was discovered 10 years ago, the biologic contribution of this posttranslational modification has remained unc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

11
204
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 200 publications
(216 citation statements)
references
References 75 publications
11
204
0
Order By: Relevance
“…It was originally shown to be localized to the cytosol in NIH3T3 and HeLa cells (22). However, studies from other laboratories suggest that SENP6 is localized in the nucleoplasm (18,23). SENP6 also appears to prefer SUMO2/3 as substrates (23).…”
Section: Localization and Enzymatic Activity Of Sumo-specific Proteasesmentioning
confidence: 99%
See 3 more Smart Citations
“…It was originally shown to be localized to the cytosol in NIH3T3 and HeLa cells (22). However, studies from other laboratories suggest that SENP6 is localized in the nucleoplasm (18,23). SENP6 also appears to prefer SUMO2/3 as substrates (23).…”
Section: Localization and Enzymatic Activity Of Sumo-specific Proteasesmentioning
confidence: 99%
“…SENP2 was reported to be tethered to the nuclear pore through binding to Nup153 nucleoporin (16,17). Furthermore, SENP2 is also localized in a yet undefined nuclear speckle that is distinct from the nuclear body (18). SENP2 has isopeptidase activity for all SUMOs.…”
Section: Localization and Enzymatic Activity Of Sumo-specific Proteasesmentioning
confidence: 99%
See 2 more Smart Citations
“…SUMO is also conjugated to coregulators of ERa and ERb, thereby modulating their ability to interact with the nuclear receptor and to activate transcription. [11][12][13] In addition, various components of the SUMO-conjugating machinery are upregulated in several malignancies: UBC9 in melanomas, ovarian cancer and lung adenocarcinomas, [14][15][16] the SUMO isopeptidase SENP1 in prostate cancer 17 and PIAS3 in breast, lung, prostate, colorectal and brain tumors. 18 By using MCF-7 human breast cancer cells overexpressing a dominant-negative mutant of UBC9 or wild type UBC9 in a mouse xenograft model it was shown that tumors expressing the UBC9 mutant exhibited reduced growth, whereas wild type UBC9 enhanced tumor growth.…”
mentioning
confidence: 99%